Transfer of post harvest technologies to small farmers - Moran, Michael J. (Dominicana Instituto Interamericano de Ciencias Agrícolas IICA, 1977)
The post harvest system needs to be tailorad to the needs of the people it serves. The area concerned in this paper is the transfer od post harvet technologies to small farmers as part of the total rural development effort, with attention being called specifically to some of the related major policy implications and issues involved.